Elucidating the Lipid Binding Properties of Membrane-Active Peptides Using Cyclised Nanodiscs - Alan H. Zhang; Ingrid A. Edwards; Biswa P. Mishra; Gagan Sharma; Michael D. Healy; Alysha G. Elliott; Mark A. T. Blaskovich; Matthew A. Cooper; Brett M. Collins; Xinying Jia; Mehdi Mobli (Frontiers in Chemistry, 2019)
The lipid composition of the cellular membrane plays an important role in a number of biological processes including the binding of membrane-active peptides. Characterization of membrane binding remains challenging, due to the technical limitations associated with the use of standard biophysical techniques and available membrane models. Here, we investigate the lipid binding properties of two membrane-active peptides, VSTx1, a well characterized ion-channel inhibitor, identified from spider venom, that preferentially binds to anionic lipid mixtures, and AA139 an antimicrobial β-hairpin peptide with uncharacterised lipid binding properties, currently in pre-clinical development. The lipid binding properties of these peptides are elucidated using nanodiscs formed by both linear and circularized (sortase-mediated) forms of a membrane scaffold protein (MSP1D1ΔH5). We find that nanodiscs formed by circularized MSPs—in contrast to those formed by linear MSPs—are sufficiently stable under sample conditions typically used for biophysical measurements (including lipid composition, a range of buffers, temperatures and concentrations). Using these circularized nanodiscs, we are able to extract detailed thermodynamic data using isothermal titration calorimetry (ITC) as well as atomic resolution mapping of the lipid binding interfaces of our isotope labeled peptides using solution-state, heteronuclear, nuclear magnetic resonance (NMR) spectroscopy. This represents a novel and general approach for elucidating the thermodynamics and molecular interface of membrane-active peptides toward flat lipid bilayers of variable composition. Our approach is validated by first determining the thermodynamic parameters and binding interface of VSTx1 toward the lipid bilayer, which shows good agreement with previous studies using lipid micelles and liposomes. The method is then applied to AA139, where the membrane binding properties are unknown. This characterization, involved solving the high-resolution structure of AA139 in solution using NMR spectroscopy and the development of a suitable expression system for isotope labeling. AA139 was found to bind exclusively to anionic membranes with moderate affinity (Kd~low μM), and was found to have a lipid binding interface involving the termini of the β-hairpin structure. The preference of AA139 for anionic lipids supports a role for membrane binding in the mode-of-action of this peptide, which is also consistent with its higher inhibitory activity against bacterial cells compared to mammalian cells. The described approach is a powerful method for investigation of the membrane binding properties of this important class of molecules.